Phenotypic characterization of the indigenous chickens (Gallus gallus) in the northwest of Algeria - Dahloum, Lahouari; Moula, Nassim; Halbouche, Miloud; Mignon-Grasteau, Sandrine (Archives Animal Breeding, 2016)
This study was conducted to characterize local chickens in the northwest of Algeria based on some phenotypic traits and to look at prediction of body weight from morphometric measurements (linear body). The results indicated that the predominant comb colour was dark red (77.8 %), followed by light red (22.2 %). Tarsus colour was either white (40.9 %), grey (31 %), yellow (15.39 %), dark (8.05 %), or green (4.51 %). Most chickens (81.7 %) had orange eyes, while 10.37 and 7.92% had yellow and dark-brown eyes, respectively. The dominant earlobe colour was white (73.96 %), followed by red (16.81 %). The remaining proportion included yellow and red-mottled yellow and black earlobes. Proportions of the adaptive genes were low. Incidences of Na, F, Pti, Cr, R, and P genes were 8.82, 0.45, 1.22, 5.54, 3.35, and 4.7 %, respectively. The calculated gene frequencies ranged from 0.002 to 0.045. Variations were also found in quantitative morphological traits. Sex-associated differences (P<0:001) were observed in almost all the parameters evaluated with higher values recorded for males. Phenotypic correlations of body weight and biometric traits ranged from 􀀀0:13 to 0.88 and 􀀀0:15 to 0.97 for males and females, respectively. From the factor analysis with varimax rotation of the intercorrelated traits, three principal components which accounted for 71.6 and 73.2% of the total variance were extracted in males and females, respectively. Orthogonal body shape characters derived from the factor analysis accounted for 84.3 and 94.2% of the variation in body weight of males and females, respectively. Information obtained from this study could be useful in an appropriate management, breeding programmes for selection and utilization of Algerian chicken genetic resources.
Keywords: indigenous chicken, phenotypic characterization, Major genes, morphometric measurements, PCA, prediction body weight